Outcomes with cilostazol after endovascular therapy of peripheral artery disease. (August 2019) - Megaly, Michael; Abraham, Bishoy; Saad, Marwan; Mekaiel, Andrew; Soukas, Peter; Banerjee, Subhash; Shishehbor, Mehdi H
The role of cilostazol after endovascular therapy (EVT) of peripheral artery disease (PAD) remains unclear. We conducted a meta-analysis for all studies reporting the outcomes of cilostazol after EVT of PAD from January 2000 through November 2018 with the outcomes of interest including primary patency, major adverse limb events (MALE), target lesion revascularization (TLR), and major amputation. We included eight studies (three randomized controlled trials (RCTs) and five observational studies) with a total of 3846 patients (4713 lesions). During a mean follow-up duration of 12.5 ± 5 months, the use of cilostazol was associated with higher primary patency (OR 2.28, 95% CI (1.77, 2.94), p < 0.001, I 2 = 24%), lower risk of TLR (OR 0.37, 95% CI (0.26, 0.52), p < 0.001, I 2 = 0%), and lower risk of major amputation (OR 0.15, 95% CI (0.04, 0.62), p = 0.008, I 2 = 0%). The use of cilostazol in RCTs was associated with significantly higher odds of primary patency compared with observational studies (OR 3.37 vs 2.28, p -interaction = 0.03). After further subgroup analysis, cilostazol remained associated with higher primary patency regardless of the use of anticoagulants (warfarin) ( p -interaction = 0.49). We conclude that the use of cilostazol after EVT of femoropopliteal and iliac lesions is associated with improved primary patency and lower risk of major amputation and TLR. The favorable impact of cilostazol is independent of the use of warfarin. PROSPERO identifier: CRD42018092715.